2023
DOI: 10.1158/2767-9764.crc-22-0410
|View full text |Cite
|
Sign up to set email alerts
|

Trends of Ovarian Cancer Incidence by Histotype and Race/Ethnicity in the United States 1992–2019

Abstract: The effect of risk factors on ovarian cancer differs by histotype, and the prevalence of such risk factors varies by race/ethnicity. It is not clear how ovarian cancer incidence has changed over time by histotype and race/ethnicity. We used the Surveillance, Epidemiology, and End Results Program (SEER-12) 1992-2019 data to examine the trend of ovarian cancer incidence for three histotypes (high-grade serous N=19,691, endometrioid N=3,212, and clear cell N=3,275) and four racial/ethnic groups (Asian/Pacific Isl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Using these 8,360 “common genes’’, we compared clusters across: (1) datasets, and (2) clustering methodologies by calculating the Pearson correlation between two vectors of moderated t-scores. To use this approach on the RNA-Seq datasets, we log10(x+1) transformed the normalized counts to more closely match the data distribution of the microarray datasets.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using these 8,360 “common genes’’, we compared clusters across: (1) datasets, and (2) clustering methodologies by calculating the Pearson correlation between two vectors of moderated t-scores. To use this approach on the RNA-Seq datasets, we log10(x+1) transformed the normalized counts to more closely match the data distribution of the microarray datasets.…”
Section: Methodsmentioning
confidence: 99%
“…Ovarian cancer is a highly fatal malignancy comprised of multiple histologically-defined subtypes (i.e., “histotypes”). High-grade serous carcinoma (HGSC) is the most common histotype (Phung et al, 2023), and an important contributor to ovarian cancer mortality (Fortner et al, 2023; Gaitskell et al, 2022; Peres et al, 2019). HGSC is also molecularly heterogeneous, which is relevant to both prognosis and treatment.…”
Section: Introductionmentioning
confidence: 99%
“…EOC is a heterogeneous disease that manifests histologically, molecularly, and clinically. Serous carcinoma is the most common histology worldwide [ 145 , 146 ], whereas the proportion of clear-cell carcinomas (CCC) is relatively higher (15–20%) in Asian countries [ 145 , 147 , 148 ].…”
Section: Timp3 In Gynaecological Cancersmentioning
confidence: 99%
“…Various risk factors are described to be associated with ovarian cancer, including older age, genetics, family history, nulliparity, and so on. 6 Studies have shown that more than 20% of ovarian cancer have a genetic susceptibility, and about 70% of these genetic abnormalities are germline mutations in the breast cancer susceptibility gene, BRCA gene. 7 Breast cancer susceptibility gene 1 ( BRCA1 ) and breast cancer susceptibility gene 2 ( BRCA2 ) are two distinct tumor suppressor genes, which play an integral role in response to cellular stress via the activation of DNA repair processes.…”
Section: Introductionmentioning
confidence: 99%